Consumo de alimentos ultraprocessados e o risco de mortalidade: uma revisão sistemática - Kathleen Krüger Peres; Rafaella Câmara Rocha Menezes; Anna Caroline Cristofoli Bertoletti; Isabella Rosa da Mata; Simone Morelo Dal Bosco (Rasbran, 2023)
ABSTRACT